Curiosity and Its Role in Cross-Cultural Knowledge Creation - Natalie S. Mikhaylov (International Journal of Emotional Education, 2016)
This paper explores the role of curiosity in promoting cross-cultural knowledge creation and competence development. It is based on a study with four international higher educational institutions, all of which offer management and business education for local and international students. The reality of multicultural and intercultural relationships is researched using constructivist grounded theory method, with data collected through indepth interviews, long-term observation and participation, and discussion of the social reality as it was experienced by the participants. The study applies the concepts of cultural knowledge development, cross-cultural competence and cultural distance. Based on the comparative analysis, curiosity emerged as a personal condition conducive to the cultural knowledge development process. The paper presents a cross-cultural competence development process model, which takes into account the cultural curiosity of the learners. The paper also provides tentative recommendations for the steps that knowledge-creating multicultural organizations can take to develop cross-cultural exchange, cultural knowledge creation and cross-cultural competence development.